2019
DOI: 10.3348/kjr.2018.0237
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomatic Three-Dimensional Threshold-Based Cardiac Computed Tomography Ventricular Volumetry in Repaired Tetralogy of Fallot: Comparison with Cardiac Magnetic Resonance Imaging

Abstract: ObjectiveTo assess the accuracy and potential bias of computed tomography (CT) ventricular volumetry using semiautomatic three-dimensional (3D) threshold-based segmentation in repaired tetralogy of Fallot, and to compare them to those of two-dimensional (2D) magnetic resonance imaging (MRI).Materials and MethodsThis retrospective study evaluated 32 patients with repaired tetralogy of Fallot who had undergone both cardiac CT and MRI within 3 years. For ventricular volumetry, semiautomatic 3D threshold-based seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 35 publications
0
26
2
Order By: Relevance
“…Other researchers have suggested that volumetric quantification using a 3D imaging modality may expedite a better understanding of the relationship between the RV status and disease severity in Ebstein anomaly [4,5]. In particular, the use of 3D threshold-based segmentation could eliminate the time-consuming and reader-dependent manual endocardial tracings for ventricular volumetry as demonstrated in previous studies [7,9]. The threshold-based approach was reported to show high reproducibility with an inter-measurement difference of 1.0±1.1%, and intraclass correlation coefficient of 1.0 [24].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Other researchers have suggested that volumetric quantification using a 3D imaging modality may expedite a better understanding of the relationship between the RV status and disease severity in Ebstein anomaly [4,5]. In particular, the use of 3D threshold-based segmentation could eliminate the time-consuming and reader-dependent manual endocardial tracings for ventricular volumetry as demonstrated in previous studies [7,9]. The threshold-based approach was reported to show high reproducibility with an inter-measurement difference of 1.0±1.1%, and intraclass correlation coefficient of 1.0 [24].…”
Section: Discussionmentioning
confidence: 92%
“…A semiautomatic 3D threshold-based segmentation method, in which the papillary muscles and trabeculations were excluded from the ventricular cavity, was used to quantify the ventricular volumes. A segmentation threshold separating the interventricular septal myocardium from the adjacent ventricular blood was regarded to be optimal [9]. The valve and venoatrial planes were manually adjusted.…”
Section: Ct Volumetric Quantificationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 a Segmentation of a cardiac CT in a 1-day-old neonate with complex double outlet right ventricle, d-malposed great vessels, and an aortic coarctation, in preparation for rapid prototyping. b 3D-printed and digital cardiac models (lateral walls removed to show intracardiac anatomy) equivalent volume assessment between CT and MRI if a CT scanner with appropriate temporal resolution is used, but mild overestimation of RV end-diastolic volumes has also been reported [59,60].…”
Section: Tetralogy Of Fallot and Other Right Ventricular Outflow Tracmentioning
confidence: 99%